2019
DOI: 10.1096/fasebj.2019.33.1_supplement.654.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interferon gamma on neutral lipid levels, lipid droplet formation, and antiviral responses in pancreatic islets and INS‐1 β cells

Abstract: Interferon (IFN)‐regulated pathways play a critical role in the development of type 1 diabetes (T1D) following exposure to environmental insults including viral infection. IFNs have been shown to modulate lipid metabolism in both immune and non‐hematopoietic cells in response to pathogens. Little is known, however, about the impact of IFN signaling on lipid metabolism in pancreatic β cells and whether IFN‐induced changes in β cell lipid metabolism are associated with antiviral responses and β cell dysfunction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Additionally, studies have reported that PLIN1-knockout mice exhibit sustained inflammation due to increased storage of lipid droplets in adipocytes [30]. Increased expression of INF-γ is associated with elevated mRNA levels of genes involved in lipid droplet formation and storage, including perilipins [31]. Consequently, it is expected that the impairment of INF-γ-mediated lipid metabolism, which plays a role in controlling fibrosis, by the 75 Gy radiation dose would result in an exacerbated fibrotic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have reported that PLIN1-knockout mice exhibit sustained inflammation due to increased storage of lipid droplets in adipocytes [30]. Increased expression of INF-γ is associated with elevated mRNA levels of genes involved in lipid droplet formation and storage, including perilipins [31]. Consequently, it is expected that the impairment of INF-γ-mediated lipid metabolism, which plays a role in controlling fibrosis, by the 75 Gy radiation dose would result in an exacerbated fibrotic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…While a correlation between IFNγ and different FFA was observed, and IFNγ participates in virus clearance by increasing chemokine production, it is already known that IFNγ induces fatty acid synthase gene expression, leading to an increase of de novo FA synthesis, explaining the observed results. Therefore, the correlation results do not seem to be related with the course of Long COVID pathology.…”
Section: Discussionmentioning
confidence: 99%